2019
DOI: 10.4274/tybd.galenos.2018.94103
|View full text |Cite
|
Sign up to set email alerts
|

Three Year Resistance Profile of <i>Acinetobacter baumannii</i> and <i>Pseudomonas aeruginosa</i> Strains Isolated from Intensive Care Units

Abstract: ÖZ Amaç: Bu çalışmada, yoğun bakım ünitesi (YBÜ) örneklerinden izole edilen Pseudomonas aeruginosa ve Acinetobacter baumannii suşlarının üç yıllık antibiyotik duyarlılıklarının incelenerek direnç oranlarındaki değişimin araştırılması amaçlanmıştır. Gereç ve Yöntem: Ocak 2015-2018 arasında YBÜ örneklerinden izole edilen Pseudomonas aeruginosa ve Acinetobacter baumannii suşlarının direnç profilleri retrospektif olarak incelendi ve yıllık direnç oranları değerlendirildi. Bulgular: Üç yıllık süre içinde YBÜ örnekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…29 In a more recent study, colistin resistance was reported at a very low rate of 5% in 420 P. aeruginosa isolated from ICUs. 33 In the present study, the colistin resistance rate was 11.7% in isolates from ICU patients. Among the reasons why colistin resistance was found to be higher in our sample group may be the inclusion of recently collected samples (2018-2021).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…29 In a more recent study, colistin resistance was reported at a very low rate of 5% in 420 P. aeruginosa isolated from ICUs. 33 In the present study, the colistin resistance rate was 11.7% in isolates from ICU patients. Among the reasons why colistin resistance was found to be higher in our sample group may be the inclusion of recently collected samples (2018-2021).…”
Section: Discussionsupporting
confidence: 42%
“…Therefore, colistin resistance has become an important issue, as shown by the many recent studies. 29,33,35 In a surveillance study conducted with data from many regions between 1997 and 2016, P. aeruginosa was one of the most common pathogenic bacterial species. It ranked first in Europe, the Asia Pacific region, and Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Turkey reported that it was isolated from respiratory tract samples (tracheal aspirate and sputum) at a rate of 65-72.7% and from blood cultures at a rate of 3.6-21%. [5,8,18] In our study, it was most commonly isolated from respiratory tract samples (59.2%) and blood cultures (23.2%).…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that the APACHE-2 score is significantly higher in patients who died from A. baumannii bacteremia patients followed in the ICU. [5,8,9] Another study stated that an APACHE-2 score of >16 could predict mortality. [14] Our study's median APACHE-2 score was 25 in patients who died, while 21 in patients who survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation